RANCANG BANGUN SISTEM PENJERNIHAN AIR OTOMATIS BERDASARKAN TURBIDITYMETER BERBASIS MIKROKONTROLLER - Affan Bachri (Jurnal Teknika, 2018)
The turbidity  sensor  works  by reading the  water particles  turbidity level captured by  the Light Dependent Resistor  (LDR)  that  has  been  emitted  by  the  laser  light.  Therefore,  the  LDR  resistance  score  changes  and  it makes  the  Nephelometric  Turbidity  Units  (NTU)  score  also  changes.  The  solenoid  valve  is  controlled  by  the suitability of the readings of the desired turbidity meter sensor by the operator.